2018
DOI: 10.1071/rj17092
|View full text |Cite
|
Sign up to set email alerts
|

Effect of GPS sample interval and paddock size on estimates of distance travelled by grazing cattle in rangeland, Australia

Abstract: The distance travelled by an animal, when determined by using global positioning system (GPS) coordinates, is usually calculated assuming linear movement between the recorded coordinates. When using long sample intervals, some movement may be overlooked if linear movement between each recorded position is assumed, because of the tendency of livestock to move in meandering paths. Conversely, overestimation of the true distance travelled could occur with short sample intervals because of the accumulation of extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 36 publications
1
24
0
Order By: Relevance
“…In general, these collars can be manufactured by companies or custom-built. According to [34], the effect of GPS sample interval and paddock size on estimates of distance traveled by grazing cattle in rangeland is an important issue to consider. The number of animals required to represent the collective characteristics of a group remains a concern in animal movement monitoring with GPS.…”
Section: Movement Ecologymentioning
confidence: 99%
“…In general, these collars can be manufactured by companies or custom-built. According to [34], the effect of GPS sample interval and paddock size on estimates of distance traveled by grazing cattle in rangeland is an important issue to consider. The number of animals required to represent the collective characteristics of a group remains a concern in animal movement monitoring with GPS.…”
Section: Movement Ecologymentioning
confidence: 99%
“…Recording of GPS at intervals in time (rather than continuously) is common because it saves battery life and allows researchers to increase the time over which data are collected (Mitchell et al 2019;Ryan et al 2004;Sahraei et al 2017). However, this practice underestimates travel distance (McGavin et al 2018;Sennhenn-Reulen et al 2017). For example, a study of Guinea baboons (Papio papio) (Sennhenn-Reulen et al 2017) examined differences in travel distance estimates from 2-h periods by subsampling GPS data collected at one fix per second, finding that travel distances were significantly shorter if less frequent GPS fixes were used in calculations.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a study of Guinea baboons (Papio papio) (Sennhenn-Reulen et al 2017) examined differences in travel distance estimates from 2-h periods by subsampling GPS data collected at one fix per second, finding that travel distances were significantly shorter if less frequent GPS fixes were used in calculations. Indeed, extensive theoretical and empirical work has shown that the temporal resolution of GPS fixes needs to match those of the behavior of interest; otherwise estimates are likely to be inappropriate (Borger et al 2006;de Weerd et al 2015;Ganskopp and Johnson 2007;Johnson and Ganskopp 2008;McGavin et al 2018;Mills et al 2006;Mitchell et al 2019;Noonan et al 2019;Postlethwaite and Dennis 2013;Rowcliffe et al 2012;Sennhenn-Reulen et al 2017;Swain et al 2008;Tanferna et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Many factors affect GPS performance including habitat type and heterogeneity [29][30][31][32], topography of the terrain [33,34], view of the sky availability [35], weather conditions [30], submersion in water [36,37], time of day [38], vegetation cover/type [33,39], GPS orientation [40], x acquisition rate [41,42], in addition to the number of available satellites and their orbiting geometry with respect to one another [43,44]. All these elements affect the propagation of signal quality and/or receiver reception capability and thus increase triangulation error (see Hofman et al [4] for review), with the latter two factors often assessed via the dilution of precision (DOP) values [44,45].…”
Section: Introductionmentioning
confidence: 99%
“…Species-speci c movements can be misinterpreted because GPS error often exaggerates the extent of movement, with error associated with distance measures being additive over time, and particularly germane at higher sampling frequencies (given that higher rates of error are incorporated per unit time) [42,46]. Indeed, although a number of authors have attempted to resolve the accuracy of GPS performance by quantifying the x success rate and location error over various scenarios [cf.…”
Section: Introductionmentioning
confidence: 99%